PHASED MARKET ACCLIMATIZATION AND PERIODIC ECONOMIC RESILIENCE: INDONESIA RESPONSE TO THE RUSSIA–UKRAINE WAR (2020–2025) - Dharma Feriawan; Ali Maksum (Indonesian Association for International Relations, 2026)
This study examines Indonesia's response to external economic shocks triggered by the Russia–Ukraine War from 2020 to 2025. It follows a phased process of market acclimatization and periodic economic resilience. Grounded in the theory of economic resilience—encompassing absorptive, adaptive, and transformative capacities—and perspectives on global supply chain restructuring, the research employs a qualitative descriptive-analytical approach. The analysis utilizes secondary trade data from TradeMap and SatuData (Ministry of Trade), exchange rate statistics from Bank Indonesia, and official trade and food policy documents to trace shifts in commodity flows, import structures, and policy responses. The findings indicate a sequential trajectory of resilience. Initial financial stabilization, reflecting absorptive capacity, occurred from 2020 to 2021. This was followed by policy recalibration, demonstrated through subsidy adjustments and import diversification, which showcased adaptive capacity from 2022 to 2023. Finally, between 2024 and 2025, structural reforms in trade configuration and food diversification signified the emergence of transformative capacity. These results suggest that Indonesia's response evolved from short-term stabilization towards progressively institutionalized economic resilience